Skalevskaya A. A. Linguastylistic and stuctural peculiarities of pantoum translation: from traditional malayan poetry to the modern Amenrican and Ukrainian literature - Skalevskaya A. A. (Philological Treatises, 2020)
The article is dedicated to the analysis of structural, linguistic and stylistic peculiarities of pantoums. Special attention is being paid to the identification of specific pragmatic and stylistic features, typical of the poetic works of such modern American poets as Donald Justice and John Ashbery. Thorough investigation is being held in the field of studying the influence of these pragmatic features being made on the level of pantoums’ translatability into the Ukrainian language.